CircFUT10 reduces proliferation and facilitates differentiation of myoblasts by sponging miR‐133a. Issue 6 (15th January 2018) - Li, Hui; Yang, Jiameng; Wei, Xuefeng; Song, Chengchuang; Dong, Dong; Huang, Yongzhen; Lan, Xianyong; Plath, Martin; Lei, Chuzhao; Ma, Yun; Qi, Xinglei; Bai, Yueyu; et al.
Abstract : Circular RNAs (circRNAs) have been identified in various tissues and cell types from human, monkey, porcine, and mouse. However, knowledge on circRNAs in bovine muscle development is limited. We downloaded and analyzed the circRNAs sequencing data of bovine skeletal muscle tissue, and further characterized the role of a candidate circRNA ( circFUT10 ) in muscle development. Quantitative real‐time PCR (qPCR) and Western blot assays were used to confirm the expression of genes involved in myoblasts differentiation and proliferation. Flow cytometry was performed to assess cell cycle distribution and cell apoptosis. EdU incorporation and CCK‐8 assay were performed to demonstrate cell proliferation. We demonstrated that circFUT10 was highly (but differentially) expressed in embryonic and adult skeletal muscle tissue. circFUT10 induced bovine primary myoblasts differentiation and increased the expression of MyoD, MyoG, and MyhC in mRNA and protein levels. circFUT10 increased the number of myoblasts in the G0/G1 phase of the cell cycle, and decreased the proportion of cells in the S‐phase. circFUT10 inhibited the proliferation of myoblasts and promoted them apoptosis. Via a luciferase screening assay, circFUT10 is observed to sponge to miR‐133a with three potential binding sites. Specifically, we show that circFUT10 regulated myoblasts differentiation and cell survival by directly binding to miR‐133a and inhibiting miR‐133a activity. Modulation of circFUT10 expression in muscle tissue may emerge as a potential target in breeding strategies attempting to control muscle development in cattle. Abstract : circFUT10 modulates SRF expression by competing for miR‐133a as a ceRNA to regulate myogenic differentiation. The ceRNA regulatory network, circFUT10/miR‐133a/SRF, sheds light on understanding the mechanisms of muscle development. Thus, modulation of circFUT10 expression in muscle tissue may emerge as potent tool to regulate muscle development in the cattle.